100 years from now: comparing parental perspectives about supports for adults with autism in the USA and China. Issue 3 (4th June 2020) - Baker, Diana; McCabe, Helen; Kelly, Mary; Jiang, Tian
Abstract : Purpose: Findings from a comparative qualitative study with parents in the USA and China increase the understanding of experiences of adults with autism in both countries. Design/methodology/approach: Semi-Structured interviews were conducted with families in the USA and in China. In total, 18 families participated in the study – 7 in the USA, 11 in China. Findings: Analysis of the comparative data led to the emergence of three overarching themes, expressing both similarities and differences in experiences: 1) transition to adult services plays out differently in the two nations, 2) parent advocacy and efforts in supporting and securing services for their children are strong in both countries but are also defined by the variability in access to services and 3) due to the scarcity of adult services in their country, Chinese parents express significantly more worries about their own aging and mortality as compared with USA parents. Research limitations/implications: Practical implications and directions for future research are discussed. Originality/value: By examining the experiences of families of adults with autism in the USA and China, the research reveals themes that would not be visible in a single-nation study.